Divergent perceptions of safety culture between occupational groups: the role of national culture. (September 2016) - Tear, Morgan J.; Reader, Tom W.; Shorrock, Steven; Kirwan, Barry
Many multinational organizations now conduct safety culture assessments at the international level. Research indicates, however, that organizational safety culture is closely tied with national culture, which has implications for how the results of international safety culture assessments are analyzed and interpreted. For example, safety culture within an organization may be influenced by national cultural tendencies for power distance, which refers to the perceived ability for how individuals of low status and influence can engage with individuals who have higher status and influence. Here we report how national power distance norms had a negative effect on the safety culture perceptions of managers, controllers, and administrative staff in Air Navigation Service Providers (ANSPs). Engineers and technical staff, however, were unaffected by national power distance norms. We also show evidence that power distance exacerbates the differences in safety culture perceptions between managers and operations staff. These data have implications for how safety culture interventions in multi-national organizations should be tailored to account for both the national cultures represented within the organization, but also for the different occupational groups that the organization consists of.